Exploring Tau-C, Tau-A, and C1M as biomarkers for Parkinson’s disease - Benmarce, Meryem; Henriksen, Kim; Karsdal, Morten; Holm Nielsen, Signe (Frontiers in Neurology, 2025)
Tau has shown to be associated with neurodegenerative diseases. In this exploratory study, we investigated the utility of blood-based biomarkers measuring Tau-C, Tau-A, and C1M in Parkinson’s disease (PD) to explore their potential as diagnostic biomarkers in two independent cohorts (TAU-C and TAU-A). We found them to discriminate between healthy donors and PD individuals (all p < 0.001), with Tau-C showing the best diagnostic discrepancy (AUROC = 0.97). Therefore, Tau-C, Tau-A, and C1M may be biomarkers for PD diagnosis.